Analysis of Patient Satisfaction on the Quality of Pharmaceutical Service at the Pharmaceutical Installation - Kharisma Jayak Pratama; Isna Nur Khasanah; Dewi Weni Sari; Nabilah Hanim Mohd Sabri (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Consumer satisfaction with services can be measured by making comparisons between what is expected by consumers on the desired quality of a service based on the reality received or felt by consumers. Pharmaceutical services are supporting services and, at the same time, one of the main centers, providing more than 90% of health services in hospitals. Objective: The purpose of this study was to describe the level of patient satisfaction and expectations and to determine the overall level of visitor satisfaction with the services of the Muhammadiyah Hospital Pharmacy Installation Siti Khodijah Gurah Kediri. Method: This type of research is a quantitative descriptive study conducted on a set of objects with the aim of knowing the level of patient satisfaction and expectations of the services of the Muhammadiyah Siti Khodijah Gurah Hospital Pharmacy Installation, Kediri. The analysis of the collected data is then made in the form of tabulations and analyzed using the percentage formula. Analysis of satisfaction level scores in this study used the Likert scale answer format, which allows patients to answer at various levels (1-4) where each answer is given a weighted value with the following conditions: score 4 if the answer is "very satisfied", score 3 if the answer is "satisfied", score 2 if the answer is "not satisfied", and score 1 if the answer is "very dissatisfied". Results: The results of measuring the level of outpatient satisfaction with service quality at the Pharmacy Installation at Siti Khodijah Gurah Kediri Hospital use five dimensions of servqual (service quality) assessment, among others, reliability, responsiveness, assurance, empathy, and tangibles (physical facilities), resulting in a negative gap value in each dimension, which means that the quality of service provided by the Pharmacy Installation at Siti Khodijah Gurah Kediri Hospital has not met patient expectations. The results of the Customer Satisfaction Index average for each dimension, namely 74.89%, are included in the satisfied category. Conclusions: The results of measuring the level of satisfaction of outpatients with the quality of service at the Pharmacy Installation at Siti Khodijah Gurah Kediri Hospital using five assessment dimensions produce a negative gap value in each dimension, which means that the quality of service provided is not in accordance with patient expectations and, based on the Customer Satisfaction Index method, is included in the satisfied category.